Schellenberg's Newman Lecture on Contemporary Philosophy of Religion: Responses and Reply - Clayton, Philip (Toronto journal of theology, 2010)
In issue 25/1 (2009), the Toronto Journal of Theology invited readers to submit responses to John L. Schellenberg, "The Philosophy of Religion: State of the Subject Report." It is the Jay Newman inaugural address delivered at the Canadian Theological Society in June 2009. Below are three responses and a reply.